2006
DOI: 10.1002/ijc.22139
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant increase of LMP1 and CD25 (IL‐2‐receptor α) expression induced by IL‐10 in the EBV‐positive NK lines SNK6 and KAI3

Abstract: Extranodal, nasal NK/T-cell lymphomas are regularly EpsteinBarr virus (EBV)-positive, with a type II latency pattern, expressing thus EBNA-1 and LMP1. The contribution of EBV to the tumor development is not known. Similarly to normal natural killer (NK) cells, cell lines derived from malignancies with a NK phenotype require IL-2 for in vitro proliferation. In our effort to explore the contribution of EBV, particularly the role of the LMP1 protein, to the pathogenesis of the NK lymphoma we found that its expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 48 publications
5
59
0
Order By: Relevance
“…As in all EBV-associated T-cell lymphoproliferative disorders, the exact mechanism by which EBV gains access and infects T cells has yet to be determined. Similar to normal NK cells and in contrast to infected B cells, EBV-infected NK cells have been found to require IL-2 for growth and proliferation even with the expression of LMP1 and other type II latency proteins [100,101]. Moreover, the reduction in LMP1 levels in treated cell lines does not lead to growth inhibition or apoptosis within the cells [102].…”
Section: Ebv and T/nk-cell Lymphoproliferative Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…As in all EBV-associated T-cell lymphoproliferative disorders, the exact mechanism by which EBV gains access and infects T cells has yet to be determined. Similar to normal NK cells and in contrast to infected B cells, EBV-infected NK cells have been found to require IL-2 for growth and proliferation even with the expression of LMP1 and other type II latency proteins [100,101]. Moreover, the reduction in LMP1 levels in treated cell lines does not lead to growth inhibition or apoptosis within the cells [102].…”
Section: Ebv and T/nk-cell Lymphoproliferative Disordersmentioning
confidence: 99%
“…This, in theory, argues against EBV involvement in the process of transformation and proliferation of the neoplastic T cells [100,101]. One study has suggested, however, that LMP1 may increase the sensitivity of the infected cell to the growth-promoting effects of IL-2 [101].…”
Section: Ebv and T/nk-cell Lymphoproliferative Disordersmentioning
confidence: 99%
“…In addition to competition with favorable cytokines, NKTL releases cytokines that are unfavorable to antitumor cells. NKTL produces IL-10, which enhances its proliferation through the upregulation of IL-2 receptor expression [16]. Because IL-10 robustly suppresses CD8 responses, NKTL would directly inhibit T-cells via IL-10 production.…”
Section: Cytokinesmentioning
confidence: 99%
“…NKTL produces IL-10 for its proliferation [16]. Because counteracting IL-10 by using a neutralizing antibody has shown antitumor effects in a melanoma model [71], this treatment would also be an option in NKTL treatment.…”
Section: Antibody Therapiesmentioning
confidence: 99%
“…We have previously shown that SNK6 cells produce several cytokines and chemokines such as interferon (IFN)-γ, interleukin (IL)-9, IL-10 and interferon-γ-inducible protein (IP)-10, which play roles in cellular proliferation and invasion in an autocrine manner [7][8][9]. Furthermore, monocytes attracted by IP-10 enhance the proliferation via cell-to-cell contact [10].…”
Section: Introductionmentioning
confidence: 99%